Unlocking the potential for optic nerve regeneration over long distances: a multi-therapeutic intervention - Zhen-Gang Liu; Zhen-Gang Liu; Lai-Yang Zhou; Lai-Yang Zhou; Lai-Yang Zhou; Lai-Yang Zhou; Yong-Quan Sun; Yong-Quan Sun; Yong-Quan Sun; Yong-Quan Sun; Yi-Hang Ma; Chang-Mei Liu; et al. (Frontiers in Neurology)
Retinal ganglion cells (RGCs) generally fail to regenerate axons, resulting in irreversible vision loss after optic nerve injury. While many studies have shown that modulating specific genes can enhance RGCs survival and promote optic nerve regeneration, inducing long-distance axon regeneration in vivo through single-gene manipulation remains challenging. Nevertheless, combined multi-gene therapies have proven effective in significantly enhancing axonal regeneration. At present, research on promoting optic nerve regeneration remains slow, with most studies unable to achieve axonal growth beyond the optic chiasm or reestablish connections with the brain. Future research priorities include directing axonal growth along correct pathways, facilitating synapse formation and myelination, and modifying the inhibitory microenvironment. These strategies are crucial not only for optic nerve regeneration but also for broader applications in central nervous system repair. In this review, we discuss multifactors therapeutic strategies for optic nerve regeneration, offering insights into advancing nerve regeneration research.